The 550th anniversary of the foundation of Kazakhstan’s statehood in 2015 an assessment from a neutral Central European country - Malek, Martin (Turkic Studies Journal, 2022)
A crucial aspect of the «politics of history» and «politics of memory» of all post-Soviet republics is the relationship to statehood. This article examines, from the perspective of a Central European observer, the commemorations held in Kazakhstan in 2015 on the occasion of the creation of the Kazakh Khanate, which is assumed to have taken place in 1465. Until recently, the history of the Kazakh Khanate was actually not an object of Eurasian research in the countries of Western Europe, although it contained many historical events and facts that influenced the history of the development of regional states and peoples. The starting point for this analysis are statements by politicians from Russia, whose importance for present-day Kazakhstan can hardly be underestimated not only in the areas of politics, economics, security, media, culture, etc., but also represents an important point of reference in questions of «history policy». Questions of the evolution of Kazakhstan‘s statehood and Kazakh ethnogenesis naturally enjoy much more attention among Kazakhstan‘s historians since 1991 than they did in Soviet times. In the present context, such topics are by no means «only» of historiographic importance, but also of eminent current political significance. Strengthening the statehood of today’s Kazakhstan as well as the faith of its citizens of all nationalities in it could contribute to counteracting possible territorial claims by individual neighbouring states. However, it is difficult to judge from the outside what influence the 2015 celebrations had on Kazakhstan’s politics and multi-ethnic society or to what extent they were able to leave lasting traces precisely there.